2009
DOI: 10.1007/s10549-009-0521-z
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of genetic variations of xenobiotic detoxification enzymes and DNA repair gene XRCC1 on the susceptibility to breast cancer

Abstract: Association between polymorphisms of X-ray repair crosscomplementation group 1 (XRCC1, at codons 194 and 399) and also several classes of glutathione S-transferases (GSTs such as GSTS1, GSTL1) and risk of breast cancer have been studied extensively [1][2][3][4][5][6]. A significant association has been found between XRCC1 Arg399Gln polymorphism and breast cancer risk [1,2]. The null genotype of GSTM1 increased the risk of breast cancer [6]. There is only one study investigating the association between genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…In total, 20 articles 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 were identified according to the inclusion and exclusion criteria. The flow chart of literature search and study selection was illuminated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 20 articles 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 were identified according to the inclusion and exclusion criteria. The flow chart of literature search and study selection was illuminated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the 20 articles, 5 of them were studies of Caucasian 9 12 15 19 27 , 10 studies were of Asian 10 11 17 18 20 24 25 26 28 29 and the rest were study of different races (white and non-white groups) 13 16 21 22 23 . Cancer cases were all diagnosed histologically or pathologically in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…There was no study examined the gene-gene and geneenvironment interactions, and so on. Finally, very recently it is reported that polymorphisms of two penetrance genes of XRCC1, and xenobiotic metabolizing enzymes have additive effect on susceptibility to breast cancer [52]. Not only for breast cancer risk, but also for other multifactorial diseases polymorphisms of low penetrance genes have additive effect on development of gastric and colorectal cancers [53][54][55] and asthma [56].…”
Section: Discussionmentioning
confidence: 99%
“…Previously we reported that the combination of members of GST classes are associated with increased risk of colorectal, gastric, and breast cancers (Saadat and Saadat, 2001;Marahatta et al, 2006;Masoudi et al, 2009Masoudi et al, , 2010Mo et al, 2009;Zhuo et al, 2009). Induction of GST subunits was deleted in the liver of Gstz1 -/ -mice.…”
Section: Resultsmentioning
confidence: 96%
“…The association between polymorphisms of several classes of GSTs (such as members of GSTy and GSTm) and several types of cancers has been extensively studied (Saadat and Saadat, 2001;Marahatta et al, 2006;Saadat, 2006;Masoudi et al, 2009Masoudi et al, , 2010Mo et al, 2009;Zhuo et al, 2009). However, there is no so much data on association between GSTz and susceptibility to cancers (Smith et al, 2001;Andonova et al, 2009).…”
Section: Introductionmentioning
confidence: 99%